Perubahan Sosio-Kultur Madrasah Aliyah Miftahul Ulum Lumajang dan Masa Depan Madrasah Pasca Berakhirnya Pandemi Covid-19 Perspektif Teori Social Engineering - Zainuddin Zainuddin (Journal of Islamic Education Research, 2021)
The Indonesian government's efforts to suppress the spread of Covid-19 directly impact the socio-cultural changes of madrasas, the phenomenon of culture shock occurring at all levels of education. This study seeks to describe and analyze the dynamics of socio-cultural changes at MA Miftahul Ulum Lumajang after the COVID-19 pandemic using social engineering theory as an analytical tool. The research method uses a phenomenological qualitative approach. The results showed: The socio-cultural changes that occurred in MA Miftahul Ulum Banyuputih Kidul Jatiroto Lumajang during the covid-19 pandemic covered various aspects, both in terms of teaching and learning activities, communication patterns between teachers and students, including the psychological aspects of teachers and students in dealing with learning activities. Teaching (KBM) to create a new paradigm for teachers and students viewing KBM that cannot be limited by space and time.